Rhoplex Acrylic Emulsions for Exterior Paints - Rohm and Haas Company. Resinous Products Division (1962)
The 1962 annual report, titled Rhoplex Acrylic Emulsions for Exterior Paints, was published by the Resins Department of the Rohm & Haas Company. This report discusses how exterior paints performed on various materials and under different exposure conditions over nine year span.
Keywords: Gums and resins, Synthetic; Emulsion paint; Painting; Rohm and Haas Company. Resinous Products Division; Corporation reports